Irreducible representations for constitutive equations of anisotropic solids II: crystal and quasicrystal classes D2m+1d, D2m+1 and C2m+1v (Archives of Mechanics - Test, 2000)
A simple, unified procedure is applied to derive irreducible nonpolynomial representations for scalar-, vector-, skewsymmetric and symmetric second order tensor-valued anisotropic constitutive equations involving any finite number of vector variables and second order tensor variables. In this part, our concern is for all crystal classes and quasicrystal classes D2m+1d , D2m+1 and C2m+1v for all integers m≥1.